عقوبة تعاطي المخدرات والاتجار بها بين الفقه الإسلامي والقانون الماليزي - يوس عزمة بنت عبدالوهاب (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2005)
This study is based upon the assumption that the recent Malaysian Laws of dangerous drugs are ineffective. The assumption is based on the increasing problem shown in police statistics. This research aims to study the Malaysian Law and compares them with Islamic Law to see their similarities and differences in dealing with punishment for drug-related offences. For this study, the researcher has followed the deductive approach that helps to thoroughly examine the views and argumentations of the early Muslim jurists, as recorded in their writings. The comparative approach is also used to compare and contrast the two systems of law. The researcher concludes that the punishment in Malaysian Law is lenient compared to that of Islamic Law. However, the punishment for drug traffickers in Malaysian Law is as severe as that of Islamic Law. Drug abuse and drug trafficking are interrelated because each exists because of the other. Drug abuse encourages trafficking and drug trafficking helps the abuser to continue his bad habit. Therefore, there is a need to balance the punishment between drug abuse and drug trafficking in order to make the Malaysian Law more effective. The researcher proposes some practical steps to make the Malaysian Law more effective in dealing with the drug scourge.